Interactive Monopoly Game: A Learning Innovation for Early Childhood Language and Social-Emotional Development - Veryawan Veryawan; Ade Tursina; Nailan Mukhriza (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study aimed to develop and evaluate an interactive language and social-emotional monopoly game designed to support early childhood development. It addresses the need for innovative learning tools in early childhood education (ECE) by integrating cognitive-linguistic stimulation and affective growth into a single interactive medium. Design/methodology/approach – The research employed a Research and Development (R&D) approach using the five-stage ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted across three ECE institutions in Langsa City, Indonesia, involving children aged 5–6 years from Group B selected through purposive sampling. Data were gathered via interviews, observations, questionnaires, and validation instruments. Findings – The developed medium successfully met all evaluation criteria. Validation by media, material, and language experts indicated that the criteria were very good, with an overall feasibility score of 94.6%. Sequential field trials (initial, main, and operational) showed consistently high feasibility, reaching up to 97%. The monopoly game effectively enhanced children’s vocabulary, communication confidence, expressive skills, emotional recognition, cooperation, empathy, and self-regulation. Research implications/limitations – The scope and generalizability of the findings are restricted to the demographic boundaries of the sample, which focused specifically on Group B children (aged 5–6 years) across three selected ECE institutions in Langsa City, Indonesia. Practical implications – This interactive game serves as a highly feasible, effective, and user-friendly tool for teachers to deliver engaging classroom instruction. It offers a practical solution for educators seeking to systematically stimulate both language acquisition and social-emotional competencies in early childhood settings. Originality/value – This study contributes to the ECE literature by transforming a conventional board game into a dual-purpose pedagogical catalyst tailored to early childhood developmental metrics. It highlights the strong potential of localized gamification for broader curriculum implementation and future educational development.